Tactile display of softness on fingertip - Frediani, Gabriele (Sci Rep, 2020)
Multi-sensory human–machine interfaces are currently challenged by the lack of effective, comfortable and affordable actuation technologies for wearable tactile displays of softness in virtual- or augmented-reality environments. They should provide fingertips with tactile feedback mimicking the tactual feeling perceived while touching soft objects, for applications like virtual reality-based training, tele-rehabilitation, tele-manipulation, tele-presence, etc. Displaying a virtual softness on a fingertip requires the application of quasi-static (non-vibratory) forces via a deformable surface, to control both the contact area and the indentation depth of the skin. The state of the art does not offer wearable devices that can combine simple structure, low weight, low size and electrically safe operation. As a result, wearable softness displays are still missing for real-life uses. Here, we present a technology based on fingertip-mounted small deformable chambers, which weight about 3 g and are pneumatically driven by a compact and cost-effective unit. Weighting less than 400 g, the driving unit is easily portable and can be digitally controlled to stimulate up to three fingertips independently. Psychophysical tests proved ability to generate useful perceptions, with a Just Noticeable Difference characterised by a Weber constant of 0.15. The system was made of off-the-shelf materials and components, without any special manufacturing process, and is fully disclosed, providing schematics and lists of components. This was aimed at making it easily and freely usable, so as to turn tactile displays of softness on fingertips into a technology ‘at fingertips’.